Izbrana vprašanja vodenja evidenc na področju dela in socialne varnosti - Tancer Verboten, Mojca (Delavci in delodajalci, 2023)
The contribution presents the role and importance of keeping labor and social security records and the issue of employers’ conduct in this area. Labor and social security records provide insight into the execution of the work process and are also important from the point of view of quality work organization. A comparison between public and private sector employers shows that the obligations of public sector employers in the field of record keeping are greater. The presented amendments to the Labour and Social Security Registers Act point to new obligations for employers.
Keywords: control over record keeping; delovno pravo; javni sektor; kadrovska evidenca; legal changes in keeping work records; personnel records in the public sector; protection of personal data; records in the field of work; Slovenija; varstvo osebnih podatkov